Secretion of glucagon-like peptide-1 in patients with type 2 diabetes mellitus: systematic review and meta-analyses of clinical studies - Calanna, S. (2013)
AIMS/HYPOTHESIS: We carried out a systematic review of clinical studies investigating glucagon-like peptide-1 (GLP-1) secretion in patients with type 2 diabetes and non-diabetic controls and performed meta-analyses of plasma total GLP-1 concentrations during an OGTT and/or meal test. METHODS: Random effects models for the primary meta-analysis and random effects meta-regression, subgroup and regression analyses were applied. RESULTS: Random effects meta-analysis of GLP-1 responses in 22 trials during 29 different stimulation tests showed that patients with type 2 diabetes (n=275) and controls without type 2 diabetes (n=279) exhibited similar responses of total GLP-1 (p=NS) as evaluated from peak plasma concentrations (weighted mean difference [95% CI] 1.09 pmol/l [−2.50, 4.67]), total AUC (tAUC) (159 pmol/l×min [−270, 589]), time-corrected tAUC (tAUC min(−1)) (0.99 pmol/l [−1.28, 3.27]), incremental AUC (iAUC) (−122 pmol/l×min [−410, 165]) and time-corrected iAUC (iAUC min(−1)) (−0.49 pmol/l [−2.16, 1.17]). Fixed effects meta-analysis revealed higher peak plasma GLP-1 concentrations in patients with type 2 diabetes. Subgroup analysis showed increased responses after a liquid mixed meal test (peak, tAUC and tAUC min(−1)) and after a 50 g OGTT (AUC and tAUC min(−1)), and reduced responses after a solid mixed meal test (tAUC min(−1)) among patients with type 2 diabetes. Meta-regression analyses showed that HbA(1c) and fasting plasma glucose predicted the outcomes iAUC and iAUC min(−1), respectively. CONCLUSIONS/INTERPRETATION: The present analysis suggests that patients with type 2 diabetes, in general, do not exhibit reduced GLP-1 secretion in response to an OGTT or meal test, and that deteriorating glycaemic control may be associated with reduced GLP-1 secretion.